Pore size evolution during sintering of ceramic oxides - Varela, José Arana [UNESP]; Whittemore, O. J.; Longo, Elson [UNESP] (Elsevier, 1990)
This paper reviews the influence of particle size distribution, agglomerates, rearrangement, sintering atmospheres and impurities on the pore evolution of some commonly studied oxides. These factors largely affect sintering mechanisms due to modifications of diffusion coefficients or evaporation-condensation. Very broad particle size distribution leads to grain growth and agglomerates densify first. Rearrangement of particles due to neck asymmetry mainly in the early stage of sintering is responsible for a high rate of densification in the first minutes of sintering by collapse of large pores. Sintering atmospheres play an important role in both densification and pore evolution. The chemical interaction of water molecules with several oxides like MgO, ZnO and SnO2 largely affects surface diffusion. As a consequence, there is an increase in the rates of pore growth and densification for MgO and ZnO and in the rate of pore growth for SnO2. Carbon dioxide does not affect the rate of sintering of MgO but greatly affects both rates of pore growth and densification of ZnO. Oxygen concentration in the atmosphere can especially affect semiconductor oxides but significantly affects the rate of pore growth of SnO2. Impurities like chlorine ions increase the rate of pore growth in MgO due to evaporation of HCl and Mg(OH)Cl, increasing the rate of densification and particle cuboidization. CuO promotes densification in SnO2, and is more effective in dry air. The rate of densification decrease and pore widening are promoted in argon. An inert atmosphere favors SnO2 evaporation due to reduction of CuO. © 1990.
Keywords: Oxides - Porosity; Particle Size Analysis; Particle Size Distribution; Sintering Mechanisms; Ceramic Materials